2007
DOI: 10.5751/es-02196-120232
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of Knowledge on Agroforestry Management Practices: the Structure of Farmer Advice Networks

Abstract: Access to knowledge on farm management practices is essential for the maintenance of productive agroforestry systems. Farmers who lack the means to acquire farming knowledge from formal sources often rely on information within their informal social networks. However, little research has explored the explicit structure of farmer communication patterns. We examined advice network structures by using farmer attributes, i.e., kin relationships, community involvement, and imitation, to characterize structural posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
113
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 153 publications
(121 citation statements)
references
References 38 publications
4
113
0
4
Order By: Relevance
“…Previous cross-sectional research has shown that farmers with access to external information through their bridging links (1) tend to use more progressive resource-conserving practices and (2) are more popular as information providers in their communities (Isaac et al 2007;Matous 2015). This experimental study contributes to the evidence that there is a causal relationship between access to external information outside of one's community and popularity as an information source inside the community.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Previous cross-sectional research has shown that farmers with access to external information through their bridging links (1) tend to use more progressive resource-conserving practices and (2) are more popular as information providers in their communities (Isaac et al 2007;Matous 2015). This experimental study contributes to the evidence that there is a causal relationship between access to external information outside of one's community and popularity as an information source inside the community.…”
Section: Discussionmentioning
confidence: 48%
“…On the other hand, external bridging links are useful for accessing locally unavailable information about sustainable natural resource management (Bodin and Crona 2009;Demiryurek 2010;Isaac et al 2007;Isaac and Matous 2017;Newig et al 2010;Newman and Dale 2007). BBoundary-spanning individuals^(i.e., individuals who connect different networks) and external links to outreach professionals are known to contribute to the innovativeness of agricultural systems (Klerkx et al 2010;Lubell et al 2011).…”
Section: Theoretical Framework: Social Network and Spatially Distribmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous research has shown that the lack of social learning and interpersonal information exchange can result in a lack of awareness and the non-adoption of resourceconserving agricultural practices (Solano et al 2003;Schneider et al 2009;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Spielman et al 2011;Conley and Udry 2010). Thus, limiting farmers' mobility may decrease farmers' access to new beneficial techniques in other communities, and farmers may in turn use less-informed and even environmentally harmful practices.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of formal institutions in disseminating necessary agricultural information across vast underdeveloped rural regions has been questioned (Matouš et al 2013b;Douthwaite et al 2001;Leeuwis 2004;Warner 2007;Spielman et al 2009;Gebremedhin and Swinton 2003), and informal social networks and social contact have been recognized as important channels for information-sharing about resource-conserving practices (Rogers 2003;Solano et al 2003;Schneider et al 2009;Ostrom 1990;Folke 2006;Janssen et al 2006;Pretty and Smith 2004;Bodin and Crona 2009;Bodin and Prell 2011;Leeuwis 2004;Hoang et al 2006;Isaac 2012;Isaac et al 2007;Warner 2007;Spielman et al 2011;Conley and Udry 2010;Bartholomay et al 2011). However, communication connections among the inhabitants of areas with less developed infrastructures tend to be geographically constrained, and the potential for the diffusion of beneficial practices between communities is thus limited (Matous et al 2013a;Apicella et al 2012;Urry 2004b).…”
Section: Introductionmentioning
confidence: 99%